A Review of Duolingo Application in Learning English - Lisa Irwit Santi; Achmad Hilal; Rismiyanto - (Channing : Journal of English Language Education and Literature, 2023)
This study aims to review the extent of the studies that have been carried out related to the Duolingo application in learning English. This study uses a descriptive quantitative research method with a content analysis approach. The data was obtained from the Google Scholar database in the form of journal articles about the Duolingo application in learning English which were published during the 2018-2022 period. The analysis was carried out by mapping the articles into three groups; the year of publication, type of research, and theme of study. The results of the study show that of 40 articles analyzed, the majority examine the use of the Duolingo application to facilitate learning vocabulary. Meanwhile, there are very few articles that examine the use of the Duolingo application to improve language skills. Therefore, in the future, researchers should conduct research on the Duolinggo application which is applied to improve English language skills.